Laboratory and field testing assessment of next generation biocide-free, fouling-resistant slippery coatings - Basu, Snehasish (2021)
Recent research efforts to combat marine biofouling have focused on foul-release coatings that are not harmful for the marine environment. Inspired by nature, Slippery lubricant infused porous surfaces (SLIPS) is a surface modification technology platform with excellent antiadhesive and antifouling capacities. Precommercial coatings based on the SLIPS concept have demonstrated promising results as an environmentally friendly strategy to combat marine biofouling. Here, we investigated the resistance against marine biofouling of a range of recently developed, biocide-free SLIPS commercial coatings. The fouling resistance performance was evaluated both in the lab and in the field by conducting multimonth immersion tests in high-fouling pressure environments. In the lab, we show that the coatings are able to largely deter settlement of marine mussels - one of the most invasive marine biofouling organisms - and to weaken their interfacial adhesion strength. The key design parameter of slippery coatings to minimize fouling is the thickness of the entrapped lubricant overlayer, which can be assessed through depth-sensing nanoindentation measurements. We find that the surface energy (i.e., hydrophobic versus hydrophilic), on the other hand, does not significantly influence the antifouling performance of these coatings in lab-scale studies. After immersion in the field in stagnant waters, all coatings exhibited efficient foul-release capacity against macrofoulers, whereas under stronger hydrodynamic flow conditions, only weakly attached biofilms were detected with a bacterial community composition that is independent of the surface energy. These results suggest that these large-scale paintable coatings exhibit a strong marine biofouling resistance with low maintenance costs, which represents an important advantage from a commercial application perspective.